74.3k views
4 votes
Negative X to the power of three times negative X to the power four times negative X to the power five

User Pallgeuer
by
5.4k points

1 Answer

6 votes

\begin{gathered} (-x)^3=(-1)^3(x)^3=-x^3 \\ (-x)^4=(-1)^4(x)^4=x^4 \\ (-x)^5=(-1)^5(x)^5=-x^5 \\ \text{hence,} \\ (-x)^3(-x)^4(-x)^5=(-x^3)(x^4)(-x^5) \\ =x^3x^4x^5 \\ =x^(3+4+5) \\ =x^(12) \end{gathered}

Negative X to the power of three times negative X to the power four times negative-example-1
User Jonathan Tran
by
6.4k points